Development of High Strength Cement-Based Concrete Utilizing Silicon Dioxide Nanoparticles and Rice Husk Ash - Najigivi, Alireza (2011)
Nano-engineering of concrete is a relatively new but rapidly growing area in concrete research. This study deals with development of high strength concrete incorporating agrowaste rice husk ash (RHA) and SiO2 nanoparticles as supplementary cementing materials replacing cement particles in order to improve sustainability of concrete constructions as fundamental need. Various binary and ternary blended concrete mixtures were produced using two sizes of RHA (5 and 95 μm) and SiO2 nanoparticles (15 and 80 nm). Fresh and hardened concretes incorporating 5, 10, 15 and 20% of RHA and 0.5, 1, 1.5, and 2% of SiO2 nanoparticles with constant water to binder ratio and aggregate content were prepared and tested. Fresh mixtures were tested for workability and hardened concretes were tested for compressive strength and water absorption at 7, 28 and 90 days of curing. Additionally,the effects of two different curing media, water and lime solution on compressive strength and water absorption of concretes were tested. Finally, using Artificial Neural Network (ANN) a model was proposed for the design procedure of concrete mixture proportioning with different sizes and contents of the utilized materials. Fresh concrete test results showed that workability of binary blends was improved in the presence of up to 20% of RHA in both particle sizes; however, workability was reduced in the presence of both sizes of SiO2 nanoparticles. In ternary blends, workability was improved in the presence of up to 20% of RHA and 2% of SiO2 nanoparticles (in both sizes). Hardened concrete test results revealed that in water-cured binary mixes compressive strength was enhanced with incorporation of both sizes of RHA up to 10%. Compressive strength of lime-cured mixtures, on the other hand, showed an increase up to 15% with coarser RHA blends but in finer RHA blends the highest strength was obtained at 20%. Similarly, the overall compressive strengths of concretes incorporating SiO2 nanoparticles were enhanced both in water-cured and limecured mixes, however, concretes comprising larger particles with contents up to 1.5% and 2% in water and lime solution, respectively, improved the compressive strength. Smaller SiO2 nanoparticles, on the other hand, improved compressive strength up to 1% and 2% in water and lime solution, respectively. In ternary blends, compressive strengths were enhanced with incorporation of RHA up to 20% and SiO2 nanoparticles (with both sizes) up to 2%. In binary blends, the lowest water absorption for water-cured RHA blends for both sizes was obtained at 10%. In lime-cured mixes, 15% of coarser RHA and 20% of finer RHA replacement yielded the lowest values at 90 days of curing. Similarly, for SiO2 nanoparticles in binary blends the lowest water absorption in both curing media across all percentages was obtained with 2% of both particle sizes at later curing ages. In ternary blends, the lowest water absorption was obtained at 90 days of curing at 2% of SiO2 nanoparticles (both sizes) in combination with 20% of RHA replacement. The overall results confirmed that ternary blends have better contributions to the mechanical and physical properties of concert due to the effects of SiO2 nanoparticles. The results also indicated that ANN is an efficient model to predict unlimited number of necessary proportions for the mixtures by conducting a limited number of experiments. The employment of the model to predict the behavior of output variables saves a lot of library trials and computational efforts carried out in conventional methods. The implications of the study for concrete engineering in general and nano-engineering of concrete in particular have been discussed.